2020
DOI: 10.1101/2020.12.16.20248342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid Aβ42 and fractalkine are associated with Parkinson’s disease with freezing of gait

Abstract: ObjectiveTo evaluate the association of Alzheimer’s disease-related and inflammation-related cerebrospinal fluid (CSF) markers with freezing of gait (FOG) in patients with Parkinson’s disease (PD).MethodThe study population included well-characterized PD patients with FOG (PD-FOG), without FOG (PD-NoFOG) and healthy controls (HC). CSF was collected using standard protocols. Three Alzheimer’s disease-related markers and 10 inflammation-related markers were measured in a Luminex 200 platform. Differences in mark… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The most established self-reporting scale used in research settings, the N-FOG-Q is acknowledged to be insufficiently sensitive for clinical trial use [ 10 ]. Previous work have shown that FOG may be associated with non-dopaminergic system changes [ 3 , 11 , 12 ], which suggests the potential for new treatments beyond dopaminergic medications like carbidopa-levodopa [ 4 ]. However, developing a novel drug that is effective in treating FOG requires accurately quantifying FOG to increase the precision for clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The most established self-reporting scale used in research settings, the N-FOG-Q is acknowledged to be insufficiently sensitive for clinical trial use [ 10 ]. Previous work have shown that FOG may be associated with non-dopaminergic system changes [ 3 , 11 , 12 ], which suggests the potential for new treatments beyond dopaminergic medications like carbidopa-levodopa [ 4 ]. However, developing a novel drug that is effective in treating FOG requires accurately quantifying FOG to increase the precision for clinical trials.…”
Section: Introductionmentioning
confidence: 99%